Optimal Operation Strategy of Ship Power System Under Battle Damage for Enhancing Survivability in Long-Term Missions - Chunhan Bai; Yun Tan; Fanrong Wei; Xiangning Lin (Energies)
After a ship suffers an external strike, the system is often in a poor state of battle damage. Currently, the support capacity of the system in all aspects decreases dramatically, the operation interval narrows, and it is not easy to ensure the completion of the long-term mission chain, especially when it involves impact loads, which is more significant. Given this, this paper proposes a restoration strategy for the power system of battle-damaged ships based on the long-term mission chain. First, the Ship Power System (SPS) is modelled and analyzed to obtain the multi-case operating characteristics of various types of loads, including impact loads under the mission chain. Second, the frequency and power support capability of energy storage is mined and quantified, and the limitations of its frequency support, power interaction, and other multi-operating states are characterized, based on which the multi-operating state switching strategy of the system containing energy storage is formed, to enhance the active support capability of the system. Subsequently, a frequency response model of the system is established. This model takes into account the support provided by energy storage, analyzes the dynamic evolution of system frequency under the disturbance of directly connected impact loads. Based on this analysis, the safe operating boundary of the system is identified. Finally, a two-stage SPS optimization model is proposed based on the above, and the effectiveness and superiority of this paper’s strategy are verified through simulation analysis of typical scenarios and comparison of multiple strategies.